Analysis of endotoxin fever in rabbits by using a monoclonal antibody to tumor necrosis factor (cachectin). - Kawasaki, H (1989)
A murine monoclonal antibody to rabbit tumor necrosis factor (TNF; cachectin) was injected intravenously into an endotoxin-treated rabbit to examine the role of endogenous TNF in fever. Both early and late peaks of biphasic fever evoked by the endotoxin injection were suppressed by the antibody. TNF activity was detected in an endotoxin dose-dependent manner in the blood 1 h after the endotoxin injection, which was coincident with the early-peak fever. Although the late-peak fever responded to the antibody, no significant TNF activity was detected in the blood obtained 1 h before the peak response. The blood was found to contain endogenous pyrogen activity, which was stable after heating at 70 degrees C for 30 min and resistant to in vitro treatment with the antibody. Rabbit TNF injection also elicited biphasic fever in rabbits, the second phase of which was found to be mediated by the similar endogenous pyrogen. These results suggest that endogenous TNF plays an important role in eliciting a febrile response to endotoxin.